Developing a monitoring and control system model for assessing performance of small scale gold mining production systems in the Philippines - Abeto, Paul Eric G. (2010)
The Philippines is one of the top producers of gold in the world. Artisanal gold mining in the Philippines is one of the metal industries that supply at least Php20 billion of the country'sGDP with thousands of people relying on the industry as their source of income. However, small-scale gold mining in the country is fairly an informal industry with minimal standards aside from the basic ones. To facilitate compettitiveness and sustainability, proper legislation and control of the industry must be present. The study developed a standard framework that would aid the mining companies and the governement mining regulatory agencies in assessing their performance such as in the environmental, economic, and operational aspects of small-scale gold mining facilities.
A performance-based management framework was used to develop the output of the research. The methodology involved 1) documentation of the operations and practices. 2) developement and identification of the best practices and appropriate criteria for small scale gold mining in the Philippines, and 3) the design of the assessment checklist to be used by the small-scale gold mining stakeholders. A monitoring and control model was developed in the form of an assessment checklist that would cover the said aspects of a small-scale gold mining facility.
The model was applied and verified by comparing actual ratings and criteria by industry and validated by evaluating test sites. Applying the assessment model with the test sites show that scale gold mining in the sites observed are not at par with all of the standards set by the study which would indicate numerous improvement opportunities as discussed in the thesis study. Usability of the model was also established through Moody's methods evaluation framework.
Results indicate that the proposed model can effectively quantify the performance of small-scale gold mining facilities in the country and can potentially be used as a tool for governement units concerned with the industry for monitoring such facilities.
"March 2010."
Thesis (M.S. Industrial Engineering)--University of the Philippines Diliman.
Keywords: Gold mines and mining -- Philippines